Development of performance indicators for sustainable enterprises - E. D. Malevskaia-Malevich (Вестник университета)
The sustainable development of industrial enterprises presupposes a qualitatively new investment level aimed at the transition to the cleanest, least resourceintensive and most waste-free production possible through a continuous process of innovation and investment projects implementation. At the same time, the current conditions for real investment are generally associated with increasing uncertainty (in particular, due to globalisation and progressive technical development), and therefore are accompanied by a high risk level, which certainly affects the ongoing projects results. The purpose of this study is to develop indicators for assessing the enterprises effectiveness, taking into account the changing external environment, the processes of transition to sustainable development of the economy. The methods of analysis, synthesis and generalisation have been applyed. The results can serve as a justification for the widely used today in practice and in economic science, but insufficiently substantiated position that in market conditions the economic efficiency of an income-generating object can be assessed by its market value. The asset owner is always interested in increasing the market value, therefore, it is generally accepted that an increase in the market value over a certain period is also an indicator of the economic efficiency of the object use by the owner, and vice versa, a decrease in the market value of a facility indicates the presence of factors impeding effective operations.